Teaching elementary mathematics - Kutz, Ronald E. (Toronto : Boston : Allyn, Bacon, 1991)
This work on the teaching of elementary mathematics is centred around the Active Teaching Model (ATM), following NCSM and NCTM guidelines on the holistic approach. This method uses cognitive processes involved in learning and integrates mathematics with other subject areas
Includes references and index.
Keywords: Mathematics -- Study and teaching (Elementary)